Developing a brand equity model for tourism destination. (2017) - Ghafari, Mohammad; Ranjbarian, Bahram; Fathi, Saeed
This paper aims to explore the specific dimensions of destination brand equity and their casual relationships to develop a model for tourism destination brand equity. For this purpose, two studies were conducted. A preliminary study was to identify the dimensions of tourism destination brand equity and the main study was conducted to test the proposed model among the tourists who visited Isfahan. The preliminary study identified eight dimensions for destination brand equity including destination brand awareness, perceived uniqueness, perceived quality, perceived brand value, destination brand image, reputation, destination brand satisfaction, and brand loyalty. The results indicated that with regard to the destination brand 1) brand awareness influences its perceived image significantly; 2) perceived uniqueness influences destination brand image significantly; 3) perceived value influences destination brand loyalty and satisfaction significantly; 4) perceived quality influences perceived value, satisfaction, and destination brand loyalty significantly; 5) destination brand image influences destination brand loyalty and destination brand value significantly; 6) destination brand reputation influences destination brand image and loyalty significantly; 7) and finally destination brand satisfaction influences destination brand loyalty significantly.